Does the age-related "anterior shift" of the P3 reflect an inability to habituate the novelty response? - Alperin, Brittany R. (2014)
Old adults often generate larger anterior neural responses than young adults when carrying out task requirements. A common finding in the ERP literature is an "anterior shift" of the P3b to targets. Utilizing principal component analysis (PCA), we recently demonstrated that rather than the P3b moving anteriorly, old adults generate a large P3a that temporally overlaps with their P3b. A dominant hypothesis for the age-related increase in anterior P3 is the failure to habituate the brain’s novelty response to rare targets. We tested this hypothesis in young and old adults by comparing the amplitude of the PCA factor representing P3a to targets presented in the first versus last of eight blocks of a visual oddball task. If, unlike young adults, old adults are unable to habituate a novelty response, one would expect 1) the P3a amplitude to decrease between the first and last blocks for young, but not old subjects and 2) the difference in P3a amplitude between young and old subjects to be greater in the last than the first block. Our results indicate the amplitude of the P3a was larger in old adults than young adults. However, this effect was not modulated by block. These findings argue against the hypothesis that an age-related increase in the P3a to targets reflects an inability of old subjects to habituate a novelty response. An alternative hypothesis is that the augmented P3a indexes the increased utilization of frontal executive functions to provide compensatory scaffolding to carry out a task.